Should Publishers and Authors be more responsible? - Berry, M. J. (Advances in Social Sciences Research Journal, 2020)
Should publishers adopt a more responsible role when publishing books that name individuals as killers in major unsolved murder cases? This paper explores what could be described as “trial by authors” and the implications this has for victims; and their families; the alleged offenders and their families and the wider Society. It will use the case of the Hammersmith Nude Murders of six female prostitutes, where six books written by six authors identified five different killers and the implications of their naming potential killers. The sexual murders occurred in and around London’s Hammersmith during 1964 to 1965. Nobody was ever convicted. This writer argues that publishers should exercise some control over publishing what would be libellous if the identified individual was still alive.